2022
DOI: 10.1590/0004-282x-anp-2021-0320
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive consequences of COVID-19: results of a cohort study from South America

Abstract: Background: Neurological and psychiatric manifestations associated with SARS-CoV-2 infection have been reported throughout the scientific literature. However, studies on post-COVID cognitive impairment in people with no previous cognitive complaint are scarce. Objective: We aim to investigate the impact of COVID-19 on cognitive functions in adults without cognitive complaints before infection and to study cognitive dysfunction according to disease severity and cognitive risk factors. Methods: Forty-five post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 41 publications
2
37
0
10
Order By: Relevance
“…Specifically, the cognitive domains mostly impaired were immediate verbal memory impairment (38% moderate, 11.2% severe) and semantic verbal fluency (34.6% moderate deficits and 8.4% severe). In addition, studies found cognitive deficits in verbal fluency, attention, executive functions, and delayed memory 12,15,27–29 . In a study by Hosp et al., 15 neurological symptoms and executive deficits correlated with frontoparietal hypometabolism in fluorodeoxyglucose (FDG)–positron emission tomography (PET).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, the cognitive domains mostly impaired were immediate verbal memory impairment (38% moderate, 11.2% severe) and semantic verbal fluency (34.6% moderate deficits and 8.4% severe). In addition, studies found cognitive deficits in verbal fluency, attention, executive functions, and delayed memory 12,15,27–29 . In a study by Hosp et al., 15 neurological symptoms and executive deficits correlated with frontoparietal hypometabolism in fluorodeoxyglucose (FDG)–positron emission tomography (PET).…”
Section: Resultsmentioning
confidence: 99%
“…The quality of case‐control and cohort studies was assessed judging three categories: the selection of the study groups, the comparability of the groups; and the ascertainment of either the exposure or outcome of interest for case‐control or cohort studies, respectively. In summary, when using the Agency for Health Research and Quality (AHRQ) threshold standards, 9 of the 20 studies were good, 15,23,25,27,29,32,33,36,31 1 was fair, 28 and 10 were poor 10–12,14,16,24,30,34,35,37 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations